Culture and technology a primer - Slack, Jennifer Daryl; Wise, J. Macgregor (John Macgregor) (Peter Lang, 2015)
Culture and Technology is an essential guide to that debate and its fascinating history. It is a primer for beginners and an invaluable resource for those deeply committed to understanding the new digital culture. The award-winning first edition (2005) has been comprehensively updated to incorporate new technologies and contemporary theories about them.